2009
DOI: 10.1590/s0102-76382009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Cistatina C e taxa de filtração glomerular em cirurgia cardíaca com circulação extracorpórea

Abstract: Cistatina C e taxa de filtração glomerular em cirurgia cardíaca com circulação extracorpórea Cystatin C and glomerular filtration rate in the cardiac surgery with cardiopulmonary bypass Abstract Objective: The aim of this study was to compare cystatin C versus creatinine as a marker for acute kidney injury in patients submitted to cardiac surgery with cardiopulmonary bypass.Methods: Fifty consecutive patients submitted to coronary artery bypass grafting were studied. Renal function was evaluated by serum cysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…The risk of AKI increases 4.8 fold for each 88 µmol/L increment in serum creatinine (SCr) levels [3-5] . AKI severe enough to require renal replacement therapy (RRT) is infrequent, but the operative mortality in these patients ranges from 40% to 80% [6] . This emphasizes the crucial importance of taking any step possible to preserve renal function in the perioperative period, especially in patients at increased risk [3,7-9] .…”
Section: Introductionmentioning
confidence: 99%
“…The risk of AKI increases 4.8 fold for each 88 µmol/L increment in serum creatinine (SCr) levels [3-5] . AKI severe enough to require renal replacement therapy (RRT) is infrequent, but the operative mortality in these patients ranges from 40% to 80% [6] . This emphasizes the crucial importance of taking any step possible to preserve renal function in the perioperative period, especially in patients at increased risk [3,7-9] .…”
Section: Introductionmentioning
confidence: 99%
“…[18-20;28;29] It holds advantages over serum creatinine in that it is unaffected by the demographic characteristics that determine muscle mass and hence serum creatinine level, and its serum levels are also unaffected by tubular secretion. [21;22] Cystatin C has been shown to be a reliable marker of GFR in patients undergoing cardiac surgery, [18][19][20] but its ability to supersede serum creatinine for monitoring changes in GFR in the immediate post-operative period (which is the most important time period for the development of AKI) remains controversial. Some studies have suggested that serum cystatin C may be able to diagnose postoperative AKI more rapidly than serum creatinine, [23] but others have been unable to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Cystatin C is a 13,25 kDa protein produced by all nucleated cells in the human body. [21] It is freely filtered in the glomerulus, then reabsorbed by epithelial cells in the proximal tubule where it is metabolized and not returned to the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney failure is one of the most important risk factors for complications after both acute ischemic cardiac events [1][2][3][4] and in cardiac surgery, causing longer hospital stays and higher in-hospital mortality [5,6]. In coronary artery bypass grafting (CABG), the previous presence of renal dysfunction is an independent predictor of operative mortality [5.7 to 12].…”
Section: Introductionmentioning
confidence: 99%